1978
DOI: 10.1136/thx.33.6.711
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerosol ipratropium bromide and salbutamol on exercise tolerance in chronic bronchitis.

Abstract: (1978). Thorax, 33,[711][712][713]. The effect of aerosol ipratropium bromide on salbutamol on exercise tolerance in chronic bronchitis. In a double-blind placebo controlled trial in 24 patients fulfilling the MRC criteria for chronic bronchitis, ipratropium bromide 40 jig and salbutamol 200 ,ug produced similar and significant (P<0001) increases in forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). A greater increase in FEV1 and FVC was seen when both drugs were used together, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 7 publications
0
32
1
Order By: Relevance
“…Although some authors have reported that cycle ergometer exercise capacity was not increased after fenoterol aerosol in COPD patients [37], other previous studies based on simple measurements such as 6-and 12-min walking test have shown encouraging results on exercise tolerance in patients with chronic airflow limitation after inhaled Pi-agonists [38][39][40], Whether the exercise perfor mance might be really improved in patients with partly reversible airway obstruction by long-term treatment with inhaled pi-agonists, is a question which needs to be more deeply addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have reported that cycle ergometer exercise capacity was not increased after fenoterol aerosol in COPD patients [37], other previous studies based on simple measurements such as 6-and 12-min walking test have shown encouraging results on exercise tolerance in patients with chronic airflow limitation after inhaled Pi-agonists [38][39][40], Whether the exercise perfor mance might be really improved in patients with partly reversible airway obstruction by long-term treatment with inhaled pi-agonists, is a question which needs to be more deeply addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven patients were extrinsic asthmatics, defined as having labile airways obstruction ( > 15 % response in FEV1 to a bronchodilator inhalation on at least three occasions), and positive skin-prick test reactions to at least two allergens. Eighteen were intrinsic asthmatics, with a bronchodilator 25 and 75 % of the total response was from salbutamol whatever the order (three patients); grade IV-> 75% of TR from either ipratropium or salbutamol whichever was given first (five patients); grade V-> 75% of TR from ipratropium if given first, % if given second (mirror image of grade II) (three patients); grade VI-> 75 % total response from ipratropium, whatever the order (mirror image of grade I) (no patients).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found synergistic effect [9][10][11][12][13][14][15], whereas others have not [16][17][18][19]. The additive effect of the two agents could be explained on the basis of differences in the mechanism of bronchodilation; anticholinergics act through the parasympathetic system whereas beta-agonists act through the sympathetic system.…”
Section: Discussionmentioning
confidence: 99%